Electrolytic copper foil and electrodes, and lithium-ion batteries using the same
By optimizing the surface characteristics of electrolytic copper foils through oblique incident X-ray diffraction, the corrosion resistance and yield strength are enhanced, addressing the safety and performance issues of lithium-ion batteries.
Patent Information
- Application Number
- JP2022163206
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-08-26
- Filing Date
- 2022-10-11
- Publication Date
- 2025-04-23
- Estimated Expiration
- 2042-10-11
AI Technical Summary
Copper foils used in lithium-ion batteries face corrosion issues due to the electrolyte, leading to reduced cycle life, reliability, and safety concerns.
The development of an electrolytic copper foil with specific surface characteristics, analyzed by oblique incident X-ray diffraction, which enhances corrosion resistance and yield strength, thereby improving the safety and performance of lithium-ion batteries.
The improved corrosion resistance and yield strength of the electrolytic copper foil result in enhanced cycle life and safety of lithium-ion batteries, making them suitable for long-term operation and high-temperature applications.
Smart Images

Figure 0007667768000004 
Figure 0007667768000005 
Figure 0007667768000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrolytic copper foil, and in particular to an electrolytic copper foil for a lithium ion battery, an electrode comprising an electrolytic copper foil, and a lithium ion battery. [Background technology]
[0002] Copper foil has good electrical conductivity and is less expensive than precious metals such as silver. Copper foil is widely used in key industries and is an important starting material in advanced technology industries. For example, copper foil can be used as an electrode material in lithium-ion batteries, which are widely used in the fields of portable electronic devices (PEDs), electric vehicles (EVs), and energy storage systems (ESSs).
[0003] When copper foil works as an electrode material in lithium ion battery, the electrolyte in lithium ion battery is corrosive to copper foil. As the operation time increases, the copper foil is corroded by the electrolyte due to long-term operation. This shortens the cycle life of lithium ion battery, reduces the reliability of lithium ion battery, and creates safety problems.
[0004] In view of this, anti-corrosion treatments are currently being attempted to be performed on copper foils in the hope of alleviating or reducing the above-mentioned problems. Common anti-corrosion treatments can be classified as cover layer protection or corrosion inhibitor protection. Cover layer protection is performed by coating a corrosion-resistant material layer on the surface of the copper foil or by electrolytic deposition of a highly corrosion-resistant metal layer on the copper foil. However, the bond strength between the copper foil and either the corrosion-resistant material layer or the highly corrosion-resistant metal layer should be considered. Once the above-mentioned cover layer is separated from the copper foil, the copper foil will corrode immediately. Meanwhile, corrosion inhibitor protection has the advantage of less volume and good effect, but brings height limitations in subsequent applications. Therefore, copper foil protected by corrosion inhibitor is not suitable for long-term operation under high temperature and can only be used in a closed circulation system.
[0005] Therefore, it is still necessary to actively seek other ways to improve the corrosion resistance of copper foil in order to improve the safety of lithium-ion batteries. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent No. 6379207 Summary of the Invention [Problem to be solved by the invention]
[0007] In view of the shortcomings of the prior art, one objective of the present disclosure is to provide an improved copper foil having excellent corrosion resistance. In particular, the improved copper foil can effectively withstand corrosion by an electrolyte. [Means for solving the problem]
[0008] In order to achieve the above-mentioned object, the present disclosure provides an electrolytic copper foil having a first surface and a second surface opposite to the first surface. The first surface and the second surface are analyzed by grazing incidence X-ray diffraction (GIXRD), and the first surface and the second surface are respectively found to have an I 1 The intensity of the characteristic peak of the (111) plane, I 2 The intensity of the characteristic peak of the (200) plane, I 3 The intensity of the characteristic peak of the (220) plane, W 1 The full width at half maximum (FWHM) of the characteristic peak of the (111) plane, given by 2 The first and second faces each have a FWHM of a characteristic peak of the (200) face represented by a ratio (I 1 +I 2 ) / (I 1 +I 2 +I 3 ), and 0.80 ° The following value (W 1 +W 2 ).
[0009] The ratio of the first and second surfaces is 0.83 or more (I 1 +I 2 ) / (I 1 +I 2 +I 3 ) and 0.80 ° The following value (W 1 +W 2 ) on each of the first and second surfaces, 1 The intensity of the characteristic peak of the (111) plane, I 2 The intensity of the characteristic peak of the (200) plane, I 3 The intensity of the characteristic peak of the (220) plane, W 1 The full width at half maximum (FWHM) of the characteristic peak of the (111) plane, given by 2 By controlling the FWHM of the characteristic peak of the (200) plane shown by:
[0010] Furthermore, the yield strength of the electrolytic copper foil can be more than 230 megapascals (MPa). Preferably, the yield strength of the electrolytic copper foil can be 231 MPa or more and 300 MPa or less. More preferably, the yield strength of the electrolytic copper foil can be 231 MPa or more and 270 MPa or less. When the yield strength of the electrolytic copper foil of the present disclosure is further controlled to exceed 230 MPa, the lithium ion battery including the electrolytic copper foil can have excellent cycle life.
[0011] Preferably, the first surface and the second surface each have a ratio (I 1 +I 2 ) / (I 1 +I 2 +I 3 More preferably, the first and second surfaces each have a ratio (I 1 +I 2 ) / (I 1 +I 2 +I 3In one embodiment, the first surface may have a ratio (I 1 +I 2 ) / (I 1 +I 2 +I 3 ) and the second surface has a ratio (I 1 +I 2 ) / (I 1 +I 2 +I 3 By controlling the intensity ratio of the characteristic peaks of the (111) plane and the (200) plane, the electrolytic copper foil can have improved corrosion resistance.
[0012] Preferably, the first surface and the second surface each have a value (W 1 +W 2 More preferably, the first and second surfaces each have a value (W 1 +W 2 In one embodiment, the first surface may have a value (W 1 +W 2 ) and the second surface has a value (W 1 +W 2 ).
[0013] In one embodiment, the first side of the electrolytic copper foil may have a root mean square height (Sq) of 0.20 μm or more and 0.55 μm or less. By controlling the Sq of the first side of the electrolytic copper foil within the range of 0.20 μm to 0.55 μm, the quality of the coating of the active material coated on the electrolytic copper foil may be improved. This makes the electrolytic copper foil suitable as an electrode material for lithium ion batteries, and the lithium ion battery comprising the electrolytic copper foil may have the advantage of high capacity. In another embodiment, the first side and the second side of the electrolytic copper foil may each have a root mean square height (Sq) of 0.20 μm or more and 0.55 μm or less. In yet another embodiment, the first side of the electrolytic copper foil may have a Sq of 0.20 or more and 0.55 or less, and the second side of the electrolytic copper foil may have a Sq of 0.25 or more and 0.50 or less.
[0014] In one embodiment, the absolute difference between the Sq of the first side and the Sq of the second side of the electrolytic copper foil can be less than 0.15 μm. In another embodiment, the absolute difference between the Sq of the first side and the Sq of the second side of the electrolytic copper foil can be less than 0.145 μm.
[0015] In one embodiment, the thickness of the electrolytic copper foil may be from 4 micrometers (μm) to 20 μm. In another embodiment, the thickness of the electrolytic copper foil may be from 6 μm to 20 μm.
[0016] The present disclosure also provides an electrode for a lithium-ion battery comprising the above-mentioned electrolytic copper foil.
[0017] The present disclosure further provides a lithium ion battery comprising the above-mentioned electrode.
[0018] According to the present disclosure, the electrolytic copper foil can be applied as the cathode of a lithium ion battery and the anode of a lithium ion battery. The above-mentioned electrolytic copper foil can be applied to a current collector. One or both surfaces of the electrolytic copper foil can be coated with at least one layer of active material to prepare an electrode of a lithium ion battery.
[0019] According to the present disclosure, the active materials can be classified into anode active materials and cathode active materials. The cathode active material contained in the cathode active material can be a carbon-containing material, a silicon-containing material, a silicon carbide composite, a metal, a metal oxide, a metal alloy, or a polymer, with carbon-containing or silicon-containing materials being preferred but not limited thereto. Specifically, the carbon-containing material can be, but is not limited to, mesophase graphite powder (MGP), non-graphitized carbon, coke, graphite, glassy carbon, carbon fiber, activated carbon, carbon black, or a polymer calcined material. The coke can include pitch coke, needle coke, or petroleum coke, etc. The polymer calcined material can be obtained by calcining phenol-formaldehyde resin or furan resin at a suitable temperature for carbonation. The silicon-containing material can have a good ability to form an alloy with lithium ions and a good ability to extract lithium ions from the lithium alloy. When the silicon-containing material is utilized in a lithium ion secondary battery, a secondary battery with a high energy density can be achieved. The silicon-containing material may be combined with cobalt (Co), iron (Fe), tin (Sn), nickel (Ni), copper (Cu), manganese (Mn), zinc (Zn), indium (In), silver (Ag), titanium (Ti), germanium (Ge), bismuth (Bi), antimony (Sb), chromium (Cr), ruthenium (Ru), molybdenum (Mo), or combinations thereof to produce an alloy. The metal or metal alloy element may be selected from the group consisting of, but is not limited to, Co, Fe, Sn, Ni, Cu, Mn, Zn, In, Ag, Ti, Ge, Bi, Sb, Cr, Ru, and Mo. Examples of the aforementioned metal oxides may be, but are not limited to, ferric oxide, ferric oxide, ruthenium dioxide, molybdenum dioxide, and molybdenum trioxide. Examples of the aforementioned polymers may include, but are not limited to, polyacetylene and polypyrrole.
[0020] In one embodiment, auxiliary additives may be added to the active material according to different needs. The aforementioned auxiliary additives may be, but are not limited to, an adhesive and / or a weak acidic agent. Preferably, the adhesive is, but is not limited to, polyvinylidene fluoride (PVDF), styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC), poly(acrylic acid) (PAA), polyacrylonitrile (PAN), or polyacrylate, and the weak acidic agent may be, but is not limited to, oxalic acid, citric acid, lactic acid, acetic acid, or formic acid.
[0021] According to the present disclosure, depending on the positive electrode active material, lithium ion batteries can be 2 Battery LiNiO 2 Battery, LiMn 2 O 4 Battery, LiCoXNI 1-X O 2 Battery or LiFePO 4 These can be classified into, but are not limited to, batteries.
[0022] According to the present disclosure, the electrolyte may include a solvent, an electrolyte, or additives that are always added when appropriate. The electrolyte solvent may include, but is not limited to, a non-aqueous solvent, for example, a cyclic carbonate ester such as ethylene carbonate (EC) or propylene carbonate (PC), a linear carbonate ester such as dimethyl carbonate (DMC), diethyl carbonate (DEC) or ethyl methyl carbonate (EMC), or a sultone. The above-mentioned solvents may be used alone or in combination of two or more solvents. The electrolyte may include, but is not limited to, lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium trifluoromethanesulfonate, lithium bis(oxalo)borate, or lithium bis(trifluoromethanesulfonimide).
[0023] In some embodiments, the electrolyte may be replaced in lithium ion batteries by a solid electrolyte, such as, but not limited to, a crystalline electrolyte, a glassy electrolyte, a glass-ceramic electrolyte, or a polymer electrolyte. Specifically, the crystalline electrolyte may be, but is not limited to, a sulfide solid electrolyte, such as lithium superionic conductor (LISICON) or silver germanite, or an oxide solid electrolyte, such as, but not limited to, a garnet-type electrolyte, a perovskite-type electrolyte, or a NASICON-type electrolyte. The glassy electrolyte may be, but is not limited to, an oxide glass electrolyte or a sulfide glass electrolyte. The glass-ceramic electrolyte may be, but is not limited to, an oxide glass-ceramic electrolyte or a sulfide glass-ceramic electrolyte. The polymer electrolyte may be, but is not limited to, a pure solid polymer electrolyte, such as polyethylene oxide-based (PEO-based) electrolytes and polypropylene oxide-based (PPO-based) electrolytes, or a gel polymer electrolyte, such as polyacrylonitrile-based (PAN-based) electrolytes, poly(methyl methacrylate)-based (PMMA-based) electrolytes, poly(vinyl chloride)-based (PVC-based) electrolytes, or poly(vinylidene fluoride)-based (PVDF-based) electrolytes.
[0024] According to the present disclosure, the lithium ion battery described above may be, but is not limited to, a laminated lithium ion battery with anode and cathode stacked through a separator, or a spirally wound lithium ion battery with continuous electrodes and separators wound in a spiral and stacked together. Depending on different products, the lithium ion battery of the present disclosure may be, but is not limited to, a cylindrical secondary battery, a square secondary battery, a pouch secondary battery, or a coin secondary battery for personal notebook computers, mobile phones, electric vehicles, and energy storage systems.
[0025] Unless otherwise specified, any parameter, condition, value, or numerical range set forth herein is understood to be expressed by the term "about." The term "about" can be expressed as within ±5% of the stated value. [Brief description of the drawings]
[0026] [Figure 1] FIG. 1 is a schematic diagram for preparing the electrolytic copper foils of Examples 1 to 12 and Comparative Examples 1 to 5. [Diagram 2] FIG. 2 is a schematic side view of the electrodeposited copper foils of Examples 1 to 12 and Comparative Examples 1 to 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0027] In the following, in order to illustrate the embodiments of the electrolytic copper foil, electrode, and lithium ion battery of the present disclosure, some embodiments are described, and some comparative examples are provided for comparison. Those skilled in the art can easily understand the advantages and effects of the present invention from the following examples and comparative examples. It should be understood that the descriptions proposed in this specification are merely preferred examples for illustrative purposes only, and are not intended to limit the scope of the present disclosure. Those skilled in the art may make various modifications and variations without departing from the spirit and scope of the present disclosure in order to practice or apply the present disclosure according to their ordinary knowledge.
[0028] As shown in Fig. 1, an apparatus for producing electrolytic copper foil includes an electrodeposition device 10, a discoloration prevention treatment device 20, and a series of guide rollers. The electrodeposition device 10 includes a cathode drum 11, an insoluble anode 12, a copper electrolyte 13, and a supply tube 14. The cathode drum 11 is a rotatable titanium cathode drum. The insoluble anode 12 is an IrO 2The insoluble anode 12 is a coated titanium plate that substantially surrounds the lower half of the cathode drum 11. The insoluble anode 12 has an anode surface 121 facing the cathode drum 11. The cathode drum 11 and the insoluble anode 12 are spaced apart from each other to accommodate the copper electrolyte 13 introduced through a supply pipe 14. The anti-tarnish treatment device 20 includes an anti-tarnish treatment tank 21 and two sets of anode plates 211a and 211b disposed in the anti-tarnish treatment tank 21. The series of guide rollers includes a first guide roller 31, a second guide roller 32, a third guide roller 33, a fourth guide roller 34, a fifth guide roller 35, and a sixth guide roller 36. The above-mentioned guide rollers can transport the raw copper foil prepared by electrodeposition to the anti-tarnish treatment device 20 for anti-tarnish treatment, and then the air knife 40 removes the excess anti-tarnish material from the surface of the anti-tarnish treated raw copper foil. After that, the anti-tarnish treated raw copper foil is further annealed by the mid-wave infrared treatment device 50, and finally the electrolytic copper foil 60 is wound on the sixth guide roller 36.
[0029] Regarding the preparation of the electrolytic copper foil of the present disclosure, the parameters of electrodeposition can be modified according to different needs. In one embodiment, the copper electrolyte used in electrodeposition may include, but is not limited to, copper sulfate, sulfuric acid, chloride ions, sodium 3-mercapto-1-propanesulfonate (MPS), and polyoxyethylene sorbitan fatty acid ester (Tween 20). In the above embodiment, the concentration of copper sulfate may be 200 grams per liter (g / L) to 400 g / L, the concentration of sulfuric acid may be 80 g / L to 150 g / L, the concentration of chloride ions may be 20 ppm to 60 ppm, the concentration of MPS may be 20 ppm to 30 ppm, and the concentration of Tween 20 may be 20 ppm to 60 ppm. In the electrodeposition step, the temperature of the copper electrolyte is 40° C. to 50° C., and the current density is 40 amperes per square decimeter (A / dm 2 ) to 50A / dm 2 It is possible.
[0030] According to the present disclosure, the properties of the electrolytic copper foil can be modified by the composition of the copper electrolyte and related parameters in the electrodeposition step. For example, the grain morphology, yield strength and root mean square height of the electrolytic copper foil can be modified by, but not limited to, the amount of Tween 20 in the copper electrolyte and the roughness (Rz) of the anode surface of the insoluble anode of the electrodeposition equipment.
[0031] In the preparation of the electrolytic copper foil of the present disclosure, the anti-tarnish treatment can be adopted according to various needs. The anti-tarnish solution adopted can be, but is not limited to, a chromium anti-tarnish solution, a nickel anti-tarnish solution, a zinc anti-tarnish solution, a tin anti-tarnish solution, etc. In one embodiment, the anti-tarnish solution can be a chromium anti-tarnish solution, which can have a concentration of chromic acid of 1.5 g / L to 5.0 g / L. The current density of the anti-tarnish treatment is 0.5 A / dm 2 t to 6.0A / dm 2 The temperature of the chrome anti-tarnish solution can be set to 20° C. to 40° C., and the duration of the anti-tarnish treatment can be, but is not limited to, 2 seconds to 4 seconds.
[0032] Regarding the preparation of the electrolytic copper foil of the present disclosure, the mid-wave infrared treatment can be adopted according to various needs. As shown in FIG. 1, after removing the excess anti-tarnish material on the surface of the anti-tarnish treated raw copper foil by the air knife 40, the anti-tarnish treated raw copper foil can be further annealed by the mid-wave infrared treatment device 50, and then the electrolytic copper foil 60 is wound on the sixth guide roller 36. In one embodiment, the mid-wave infrared annealing treatment can be applied to one or both sides of the electrolytic copper foil. Regarding the mid-wave infrared annealing, the temperature of the lamp filament is in the range of 1500° C. to 1800° C., the maximum wavelength is 1.4 micrometers (μm) to 1.8 μm, the distance between the mid-wave infrared treatment device and the electrolytic copper foil is 30 millimeters (mm) to 60 mm, and the annealing time can be 5 seconds (sec) to 15 seconds (sec). The grain morphology, yield strength and root mean square height of the electrolytic copper foil can be modified by, but not limited to, the annealing time.
[0033] electrolytic copper foil
[0034] Examples 1 to 12: Electrolytic copper foil The electrolytic copper foils of Examples 1 to 12 were produced by the same electrodeposition step, discoloration prevention treatment step and mid-wave infrared annealing step using the manufacturing apparatus of Figure 1. The production method of the electrolytic copper foils of Examples 1 to 12 was as follows.
[0035] First, the copper electrolyte 13 used in the electrodeposition step was prepared. During the electrodeposition step, the cathode drum 11 was rotated at a constant speed on a fixed shaft, and a current was applied between the cathode drum 11 and the insoluble anode 12, causing the copper ions in the copper electrolyte 13 to be electrodeposited on the surface of the cathode drum 11 to form raw copper foil. Next, the raw copper foil was peeled off from the cathode drum 11 and guided to the first guide roller 31.
[0036] Here, the composition of the copper electrolyte 13 and the parameters of the electrodeposition step were as described below: I. Composition of copper electrolyte 13: Copper sulfate (CuSO 4 5H 2 O): approx. 320g / L, Sulfuric acid: approx. 110g / L, Chloride ion (Cl - ): approx. 25ppm, Sodium 3-mercapto-1-propanesulfonate (MPS, purchased from HOPAX): approximately 20 ppm, and Tween 20: concentrations shown in Table 1. II. Parameters of electrodeposition step: Temperature of copper electrolyte 13: about 50°C, Rz of the anode surface: as shown in Table 1, and Current density: about 50A / dm 2 .
[0037] The above Rz of the anode surface is the maximum height as defined by JIS B0601-1994. The equipment and parameters for measuring the Rz of the anode surface were as follows: I. Measuring equipment: Small surface roughness measuring instrument (contact mode) SJ-410, purchased from Mitutoyo Corporation. II. Measurement parameters: Needle tip radius: 2μm, Needle tip angle: 60°, Cut-off length (λc): 0.8 mm, and Evaluation length: 4mm.
[0038] Thereafter, the raw copper foil was transported to the tarnish prevention treatment device 20 by the first guide roller 31 and the second guide roller 32, and the raw copper foil was immersed in the tarnish prevention treatment bath 21 filled with a chromium tarnish prevention treatment solution. Next, the two opposite sides of the raw copper foil were subjected to tarnish prevention treatment by two sets of anode plates 211a and 211b through transport by the third guide roller 33, so that a first tarnish prevention layer and a second tarnish prevention layer were electrodeposited on the two opposite sides of the raw copper foil.
[0039] Wherein, the composition of the chrome anti-tarnish solution and the parameters of the anti-tarnish treatment are as follows: I. Composition of chrome anti-tarnish solution: Chromic acid (CrO 3 ): approx. 1.5g / L, II. Anti-tarnish treatment parameters: Solution temperature: 25°C, Current density: about 0.5A / dm 2 , and Processing time: about 2 seconds.
[0040] After the tarnish prevention treatment was completed, the tarnish prevention-treated copper foil was guided to the fourth guide roller 34. The excess tarnish prevention material was removed from the surface by the air knife 40, and the tarnish prevention-treated copper foil was dried. Then, the above-mentioned tarnish prevention-treated copper foil was conveyed to the mid-wave infrared treatment device 50 by the fifth guide roller 35, and the two sides of the tarnish prevention-treated copper foil were annealed, and finally, the electrolytic copper foil 60 was obtained and wound on the sixth guide roller 36.
[0041] Here, the annealing conditions are as follows: I. Parameters of mid-wave infrared processing equipment 50: Lamp tube diameter: 23×11mm / 34×14mm, Lamp filament temperature, 1600±10℃; Maximum wavelength: 1.4μm to 1.8μm, Maximum power: 120 kilowatts per square meter (kW / m 2 ), and Maximum linear power density: 80 watts per centimeter (W / cm). II. Annealing treatment parameters: The distance between the lamp tube and the electrolytic copper foil to be annealed is 45 mm. Output: 95% and Annealing time: as shown in Table 1.
[0042] The above-mentioned method resulted in electrolytic copper foils of about 6 μm thickness in Examples 1 to 8, 11 and 12, electrolytic copper foils of about 4 μm thickness in Example 9, and electrolytic copper foils of about 20 μm thickness in Example 10. The differences between Examples 1 to 12 were the thickness of the electrolytic copper foil, the concentration of Tween 20 in the copper electrolyte, the roughness of the anode surface in the electrodeposition step, and the annealing time. As shown in FIG. 2, the electrolytic copper foil 60 of each Example comprises a copper layer 61 (corresponding to the raw copper foil not treated with the anti-tarnish treatment), a first anti-tarnish layer 62, and a second anti-tarnish layer 63. The copper layer 61 comprises an electrodeposition side 611 and a drum side 612 opposite to the electrodeposition side 611. During electrodeposition, the electrodeposition side 611 was the surface of the raw copper foil facing the insoluble anode, and the drum side 612 was the surface of the raw copper foil in contact with the cathode drum. The first tarnish prevention layer 62 is formed on the electrodeposited side 611 of the copper layer 61, and the first tarnish prevention layer 62 has an outermost first surface 621. The second tarnish prevention layer 63 is formed on the drum side 612 of the copper layer 61, and the second tarnish prevention layer 63 has an outermost second surface 631. The first surface 621 and the second surface 631 are the two outermost surfaces of the electrolytic copper foil 60 and face each other.
[0043] Comparative Examples 1 to 5: Electrolytic copper foil The electrolytic copper foils of Comparative Examples 1 to 5 were provided for comparison with Examples 1 to 12. The methods for preparing the electrolytic copper foils of Comparative Examples 1 to 5 were similar to those of Examples 1 to 12, except for the thickness of the electrolytic copper foil, the concentration of Tween 20 in the copper electrolyte, the Rz of the anode surface in the electrodeposition step, and the annealing time. The parameters are all listed in Table 1. Furthermore, the electrolytic copper foils of Comparative Examples 1 to 5 have the same structure as that shown in FIG. 2, and all of the electrolytic copper foils have a thickness of 6 μm.
[0044] Table 1: Thickness of electrolytic copper foils of Examples 1 to 12 (E1 to E12) and Comparative Examples 1 to 5 (C1 to C5), and the concentration of Tween 20 in the copper electrolyte, Rz of the anode surface, and annealing time in the preparation of E1 to E12 and C1 to C5
[0045] [Table 1]
[0046] Test Example 1: Grazing Incidence X-ray Diffraction (GIXRD) Using an X-ray diffractometer, the electrolytic copper foils of Examples 1 to 12 and Comparative Examples 1 to 5 were measured as test samples, and an oblique incidence X-ray diffraction experiment was carried out. In this experiment, the I of the first surface and the second surface of each test sample was measured. 1 The intensity of the characteristic peak of the (111) plane, I 2 The intensity of the characteristic peak of the (200) plane, I 3 The intensity of the characteristic peak of the (220) plane, W 1 The FWHM of the characteristic peak of the (111) plane, and W 2 The FWHM of the characteristic peak of the (200) plane, given by
[0047] After the calculation, the ratio of the first surface of each of the electrodeposited copper foils of Examples 1 to 12 and the comparative example (I 1 +I 2 ) / (I 1 +I 2 +I 3 ), the value of the first face (W 1 +W 2 ), the ratio of the second face (I1 +I 2 ) / (I 1 +I 2 +I 3 ), and the value of the second surface (W 1 +W 2 ) was obtained. The results are listed in Tables 2 and 3 below.
[0048] Here, the equipment and parameters for the grazing incidence X-ray diffraction experiment are as follows: I. Measuring equipment: X-ray diffractometer: Bruker D8ADVANCE Eco. II. Measurement parameters: Angle of incidence: 0.8°.
[0049] Test Example 2: Yield Strength As test samples, the electrodeposited copper foils of Examples 1 to 12 and Comparative Examples 1 to 5 were analyzed according to IPC-TM-650 2.4.4.18 to obtain stress-strain curves with the X-axis being strain (ε) and the Y-axis being stress (σ). A parallel line to the Y-axis was drawn at a strain of 0.5%, and the yield strength was determined by the stress corresponding to the intersection of the line with the stress-strain curve. The results are listed in Table 3.
[0050] Here, the instruments and parameters for measuring the yield strength of the electrolytic copper foil are as follows: I. Measuring equipment: AG-I universal testing machine, purchased from Shimadzu Corporation II. Measurement parameters: Sample size: 100mm (length) x 12.7mm (width), Chuck distance: 50mm, and Crosshead speed: 50mm / min.
[0051] Test Example 3: Root Mean Square Height (Sq) The electrolytic copper foils of Examples 1 to 12 and Comparative Examples 1 to 5 were used as test samples. The root mean square height (Sq) of the first and second surfaces of each test sample was measured under the following conditions and was defined by ISO25178-2:2012. The results are listed in Table 3.
[0052] Here, the instrument and parameters for measuring the Sq of the electrolytic copper foil are as follows: I. Measuring equipment: Laser scanning confocal microscope: LEXT OLS5000-SAF, purchased from Olympus Corporation; Objective lens: MPLAPON-100xLEXT. II. Measurement conditions: Light source wavelength: 405nm, Magnification of objective lens: 100x, Optical zoom: 1.0x, Observation area: 129μm × 129μm; Resolution: 1024 pixels x 1024 pixels, Mode: Auto tilt elimination, Filter: No filter, Temperature: 24±3℃, and Relative humidity:63±3%.
[0053] Test Example 4: Corrosion resistance As test samples, the above-mentioned electrolytic copper foils of Examples 1 to 12 and Comparative Examples 1 to 5 were cut into test pieces of 10 cm x 10 cm. The test pieces were immersed in a lithium electrolyte of a lithium ion battery at 60 ° C for 24 hours, then removed from the solution and placed in an oven at 60 ° C to remove the solution on the test pieces. The appearance of the test pieces was visually observed to evaluate whether discoloration occurred. The lithium electrolyte was a 1 molar (M) solution of lithium hexafluorophosphate solute dissolved in a mixed solvent of ethylene carbonate (EC) and diethyl carbonate (DEC) having a volume ratio of 1:1. If partial discoloration was observed on the test pieces, indicating that the electrolytic copper foil has poor corrosion resistance to the electrolyte, it was classified as "X". In contrast, if no discoloration occurred anywhere in the entire test pieces, indicating that the electrolytic copper foil has good corrosion resistance to the electrolyte, it was classified as "O". The evaluation results are listed in Tables 2 and 3.
[0054] electrode
[0055] Examples 1A to 12A and Comparative Examples 1A to 5A: Cathode The first and second sides of the electrolytic copper foils of Examples 1 to 12 and Comparative Examples 1 to 5 were each coated with a cathode slurry containing an anode active material that would become the anode of a lithium ion battery. In detail, the anode was prepared by the following steps.
[0056] First, a cathode slurry was prepared. The composition of the cathode slurry is as follows: Mesophase graphite powder (MGP): 93.9 parts by weight, serving as the cathode active material; Conductive carbon black (Super P): 1 part by weight, acts as a conductive additive; Polyvinylidene fluoride (PVDF6020): 5 parts by weight, acts as a solvent binder; Oxalic acid: 0.1 parts by weight, and N-methylpyrrolidone (NMP): 60 parts by weight.
[0057] Next, the cathode slurry was coated on the first surface and the second surface of each of the electrolytic copper foils to a coating thickness of 200 μm for each surface, and then dried in an oven at 160° C. and pressed by a press to obtain cathodes of Examples 1A to 12A and Comparative Examples 1A to 5A.
[0058] Here, the coating conditions and pressing conditions for producing the cathode are as follows: I. Coverage conditions: Coating speed: 5 meters / minute (m / min), and Coating thickness: Approximately 200 μm on each side. II. Pressing conditions: Press processing speed: 1m / min, Pressing pressure: 3000 pounds per square inch (psi); Press roller size: 250mm (outer diameter, φ) x 250mm (width), Roller hardness: 62 to 65HRC, and Roller material: high carbon chromium bearing steel (SUJ2).
[0059] Test Example 5: Coating Quality The cathodes of Examples 1A to 12A and Comparative Examples 1A to 5A were used as test samples to evaluate whether the active material exhibited good coating quality when the electrodeposited copper foil was coated with the active material in the preparation of the cathode. Each test sample was visually observed on two surfaces to determine whether folds or wrinkles were formed on the surface of each test sample. If folds or wrinkles were observed on either surface of the test sample, the test sample was classified as "△", indicating that the test sample exhibited poor coating quality. If no folds or wrinkles were observed on the two surfaces of each test sample, the test sample was classified as "O", indicating that the test sample exhibited the expected coating quality. The results are listed in Table 3.
[0060] Lithium-ion battery
[0061] Examples 1B to 12B and Comparative Examples 1B to 5B: Lithium-ion batteries The lithium ion batteries of Examples 1B to 12B and Comparative Examples 1B to 5B were prepared by combining the negative electrodes of Examples 1A to 12A and Comparative Examples 1A to 5A with the same positive electrodes, respectively. For illustrative purposes, the process of preparing the lithium ion batteries by using the above-mentioned negative electrodes was as follows:
[0062] First, an anode slurry was prepared. The composition of the anode slurry was as follows: LiCoO 2 : 89 parts by weight, acting as an anode material; Flake graphite (KS6): 5 parts by weight, acts as a conductive additive; Conductive carbon black (Super P): 1 part by weight, acts as a conductive additive; Polyvinylidene fluoride (PVDF1300): 5 parts by weight, acts as a solvent binder; N-methylpyrrolidone (NMP): 195 parts by weight.
[0063] The anode slurry was then coated onto two surfaces of an aluminum foil. After the solvent was evaporated, the anode and cathode from each of the examples and comparative examples were cut to a specific size, and then the anode and cathode were alternately stacked with a microporous separator (model: Celgard 2400, manufactured by Celgard Co., Ltd.) in between, and then placed in a pressing mold (model: LBC322-01H, purchased from Shenzhen Capchem Technology Co., Ltd.) filled with electrolyte and sealed to form a stacked lithium ion battery. The stacked lithium ion battery had a size of 41 mm x 34 mm x 53 mm.
[0064] Test Example 6: Ability The lithium ion batteries of Examples 1B to 12B and Comparative Examples 1B to 5B were used as test samples. Using the following test conditions, the five cycle capacities of each of the lithium ion batteries were recorded and compared with each other. The results are listed in Table 3.
[0065] Here, the test conditions for each charge-discharge cycle are as follows: Charge mode: constant current constant voltage (CCCV), Discharge mode: constant current (CC), Charging voltage: 4.2V, Charging current: 0.2C, Discharge voltage: 2.8V, Discharge current: 0.2C, and Test temperature: Approximately 55°C.
[0066] Examination of experimental results The results of Test Examples 1 to 6 above are summarized in Tables 2 and 3.
[0067] As shown in Table 2, the first and second sides of the electrodeposited copper foils of Examples 1 to 12 analyzed by GIXRD each had a ratio (I 1 +I 2 ) / (I 1 +I 2 +I 3 ), and 0.80 ° Less than (W1 +W 2 ), these electrolytic copper foils could effectively resist corrosion by the electrolyte in the lithium ion battery. That is, these electrolytic copper foils had good corrosion resistance to the electrolyte.
[0068] Table 2: (I) of the first and second sides of the electrodeposited copper foils of Examples 1 to 12 (E1 to E12) and Comparative Examples 1 to 5 (C1 to C5) 1 +I 2 ) / (I 1 +I 2 +I 3 ) and the first and second surfaces (W 1 +W 2 ), and the evaluation results of the corrosion resistance of electrolytic copper foil to electrolyte
[0069] [Table 2]
[0070] On the other hand, in the case of the electrodeposited copper foils of Comparative Examples 1 to 5, the first and second sides of each electrodeposited copper foil had a ratio (I 1 +I 2 ) / (I 1 +I 2 +I 3 ) and 0.80 ° The following value (W 1 +W 2 ) at the same time, this electrodeposited copper foil could not have the necessary corrosion resistance against the electrolyte. The electrodeposited copper foils of Comparative Examples 1 to 5 were not useful for use in lithium ion batteries.
[0071] Further investigation of the results of Comparative Examples 1 to 5 revealed that the electrodeposited copper foils of Comparative Examples 1 and 4 had a ratio (I 1 +I 2 ) / (I 1 +I 2 +I 3 ) and 0.80 ° Values exceeding (W 1 +W 2) to the first surface, it was not possible to exhibit good corrosion resistance. 1 +I 2 ) / (I 1 +I 2 +I 3 The electrodeposited copper foil of Comparative Example 2 has a first surface of 0.80 ° Values exceeding (W 1 +W 2 ) and therefore could not exhibit good corrosion resistance. ° The following value (W 1 +W 2 The electrodeposited copper foils of Comparative Examples 3 and 5, which have a ratio (I 1 +I 2 ) / (I 1 +I 2 +I 3 ), it was not possible to exhibit good corrosion resistance. 1 +I 2 ) / (I 1 +I 2 +I 3 ) and the appropriate value (W 1 +W 2 It can be seen that the first and second surfaces of the electrolytic copper foil having both of the above-mentioned properties can ensure the electrolytic copper foil having good corrosion resistance to the electrolyte.
[0072] Furthermore, other experimental significance can be obtained from the combined results of GIXRD analysis and Sq for the electrodeposited copper foil. As shown in Table 3, the first side of each of the electrodeposited copper foils of Examples 1 to 10 has a ratio (I 1 +I 2 ) / (I 1 +I 2 +I 3 ) and 0.80 ° The following value (W 1 +W 2), and further had a suitable Sq (0.20 μm to 0.55 μm). As a result, these electrolytic copper foils not only had good corrosion resistance to the electrolyte, but also exhibited good coating quality after being coated with active materials. Therefore, the prepared lithium ion batteries of Examples 1B to 10B had high capacity characteristics. More specifically, the lithium ion batteries of Examples 1B to 10B each had a capacity of more than 300 mAh / g at the fifth charge-discharge cycle.
[0073] Table 3: (I) of the first and second sides of each of the electrodeposited copper foils E1 to E12 and C1 to C5 1 +I 2 ) / (I 1 +I 2 +I 3 ), the first and second surfaces (W 1 +W 2 ), Sq of the first and second faces, the absolute difference in Sq between the first and second faces (AD), the yield strength (σ y ), corrosion resistance, and coating quality, and the performance of lithium-ion batteries in the fifth charge-discharge cycle.
[0074] [Table 3]
[0075] In contrast, the electrolytic copper foils of Examples 11 and 12 and Comparative Examples 3 and 4 could not have good coating quality after being coated with active material, because the first side did not have Sq within a suitable range. Furthermore, the lithium ion batteries prepared in Examples 11B and 12B and Comparative Examples 3B and 4B had capacities of less than 300 mAh / g in the fifth charge-discharge cycle, which is much lower than the capacities of the lithium ion batteries of Examples 1B to 10B. This indicates that they are not very applicable to end products that require high capacity.
[0076] In conclusion, the intensities of the characteristic peaks of the (111) planes of the first and second planes (I 1), the intensity of the characteristic peak of the (200) plane (I 2 ), the intensity of the characteristic peak of the (220) plane (I 3 ), and the FWHM of the characteristic peak of the (111) plane (W 1 ), FWHM of the characteristic peak of the (200) plane (W 2 ) is beneficial to improve the corrosion resistance of the electrolytic copper foil to the electrolyte, thereby improving the safety of the lithium ion battery.
[0077] In addition, the Sq of the first side of the electrolytic copper foil can be further controlled according to different needs, so that the electrolytic copper foil has good coating quality after being coated with active material, and the lithium ion battery can further have improved capacity.
[0078] Although numerous characteristics and advantages of the present disclosure have been set forth in the above description, together with details of the structure and characteristics of the disclosure, the disclosure is merely illustrative, and within the scope of the principles of the disclosure, changes may be made in details, particularly in matters of material, shape, size and configuration of parts, to the full extent indicated by the broad general meaning of the terms in which the appended claims are expressed.
Claims
1. An electrolytic copper foil having a first surface and a second surface opposite to the first surface, The first surface and the second surface are analyzed by grazing incidence X-ray diffraction, and the first surface and the second surface are each determined to be I 1 The intensity of the characteristic peak of the (111) plane, I 2 The intensity of the characteristic peak of the (200) plane, denoted by I 3 The intensity of the characteristic peak of the (220) plane, denoted by W 1 The full width at half maximum of the characteristic peak of the (111) plane, represented by 2 and having a full width at half maximum of the characteristic peak of the (200) plane represented by The first surface and the second surface each have a ratio (I 1 +I 2 ) / (I 1 +I 2 +I 3 ), and values of 0.80° or less (W 1 +W 2 ).
2. The electrolytic copper foil according to claim 1, characterized in that the electrolytic copper foil has a yield strength of more than 230 MPa.
3. The first surface and the second surface each have a ratio (I 1 +I 2 ) / (I 1 +I 2 +I 3 The electrolytic copper foil according to claim 1, characterized in that it has a thickness of 100 nm or less.
4. The first surface and the second surface each have a value of 0.25° or more and 0.75° or less (W 1 +W 2 The electrolytic copper foil according to claim 1, characterized in that it has a thickness of 100 nm or less.
5. The electrolytic copper foil according to claim 1, wherein the electrolytic copper foil has a yield strength of 231 MPa or more and 300 MPa or less.
6. The electrolytic copper foil according to claim 1 , wherein the first surface has a root-mean-square height (Sq) of 0.20 μm or more and 0.55 μm or less.
7. The electrolytic copper foil according to claim 6, wherein the second surface has a root mean square height (Sq) of 0.20 μm or more and 0.55 μm or less.
8. The electrolytic copper foil according to claim 7, wherein an absolute difference between the Sq of the first surface and the Sq of the second surface of the electrolytic copper foil is less than 0.15 μm.
9. An electrode for a lithium ion battery comprising the electrolytic copper foil according to any one of claims 1 to 5.
10. A lithium ion battery comprising the electrode according to claim 9.
Citation Information
Patent Citations
Preparation method of millimeter-level rectangular monolayer monocrystal graphene
CN109112616A
Manufacture of magnetic head
JP1988079207A
Electrolytic copper foil, current collector for lithium secondary battery, including the same, and lithium secondary battery
JP2017079208A
Composite copper foil, printed-circuit board, electronic device, and production method of composite copper foil
JP2020180366A
Flexible copper foil laminate film, electronic device including same, and method for manufacturing said flexible copper foil laminate film
JP2022517051A